Trend Analysis Of ESG Disclosure On Green Finance Performance In Indonesia, Malaysia & Singapore Exchanges - Azwani Aulia; Fiona Febriyanti; Lita Permata Umi (Universitas Serang Raya, 2023)
Green Finance in the banking sector is a new issue in the financial world because it is considered capable of increasing economic growth, by conserving natural resources so that economic development continues to be sustainable. This study aims to determine what factors affect financial performance in disclosing ESG items, so that company management can imply the results of this study which are expected to provide direct or indirect benefits for companies in the banking sector. The author collects independent variables related to the research, namely operational performance, financial performance, with firm value as an intervening variable. The population of this study is the banking sector companies listed on the Indonesia, Malaysia and Singapore Stock Exchanges. This study uses quantitative methods with secondary data using multivariate analysis with a structural equation modeling-partial least square (SEM-PLS) approach. The main challenge in implementing green investment is the lack of incentives from the government and stakeholders. This is indicated by the results of the H1 study; H3; H4; H6; H7 has a significant result because it has a p value below 0.05. While H2; H3; H5; H8; H9; H10 has an insignificant result because it has a p value above 0.05. Responding to the challenges of sustainable finance requires policy tools from various relevant ministries and institutions. Suggestions for future researchers are to try to re-examine using other test tools, such as SPSS or eviews.